1985
DOI: 10.1073/pnas.82.20.7096
|View full text |Cite
|
Sign up to set email alerts
|

3'-Azido-3'-deoxythymidine (BW A509U): an antiviral agent that inhibits the infectivity and cytopathic effect of human T-lymphotropic virus type III/lymphadenopathy-associated virus in vitro.

Abstract: The acquired immune deficiency syndrome (AIDS) is thought to result from infection of T cells by a pathogenic human retrovirus, human T-lymphotropic virus type III (HTLV-III) or lymphadenopathy-associated virus (LAV). In this report, we describe the antiviral effects of a thymidine analogue,3'-azido-3'-deoxythymidine (BW A509U), which, as a triphosphate, inhibits the reverse transcriptase of HTLV-III/LAV. This agent blocks the expression of the p24 gag protein of HTLV-III/LAV in H9 cells following exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
656
2
12

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,678 publications
(695 citation statements)
references
References 27 publications
(28 reference statements)
13
656
2
12
Order By: Relevance
“…3 A) . The value of 25 nM AZT for 50% inhibition of virus production is in accord with inhibitory concentrations measured by p24 production (29), plaque formation (23), or cell-free reverse transcriptase activity (30) .…”
Section: Resultsmentioning
confidence: 63%
“…3 A) . The value of 25 nM AZT for 50% inhibition of virus production is in accord with inhibitory concentrations measured by p24 production (29), plaque formation (23), or cell-free reverse transcriptase activity (30) .…”
Section: Resultsmentioning
confidence: 63%
“…Treatment with cyclosporin A (40 and 60/mg/kg/day) before and after infection with LP-BM5 MuLV significantly inhibited the development of immunologic and histopathologic changes characteristic of MAIDS [15]. This study extends our analysis by using cyclosporin A at lower doses either alone or combined with zidovudine, an inhibitor of retroviral reverse transcriptase [16].…”
supporting
confidence: 49%
“…Using human host-cellbased screening systems, it was possible to identify AZT as a candidate for development and, with unprecedented speed, enter it into clinical testing (4). In randomized placebo-controlled trials, AZT was rapidly shown to have therapeutic value and has subsequently become the "drug of choice" for treatment of AIDS (5).…”
mentioning
confidence: 99%